A categoria trabalho na produção do conhecimento do serviço social a partir do legado da Modernidade e as inflexões do Pós-Moderno - Lima, Ingridy Lammonikelly da Silva (2018)
The present study sought to approach the reality of Social work, through the theoretical-methodological dimension, in a research carried out in the Graduate Programs in Social Work of Brazil. The theoretical section that connects us with the totality is the Work Category, since the analysis focused on the Programs with lines and areas in Work, with Dissertations that had the object of study the Work. The main objective of this study is the analysis on the production of knowledge of Social Work concerning the Labor Category from the legacy of Modernity and the postmodern inflections. While unfolding will be specifically examined the "State of the Art" of the work category in master's dissertations, linked to Programs with lines and areas in Work. An analytical inventory of the lines of research and areas of concentration around the Labor Category, as well as the investigation of the theoretical field in which the Social Work production on the Labor Category is placed, is based on the legacy of the Modernity and the inflections of Postmodernity. The analytical assumption coming from the successive approximations with the object of study is that the Social Work has been suffering inflections from the process of reorganization of capitalism since the structural crisis that began in 1970. Thus, it is a bibliographical and documentary research , carried out by the following categories of analysis: Social Work, Work and Knowledge Production. The research is divided into two moments. In the first one, we carried out the survey of the 34 Post-Graduate Programs in Social Work, reaching the quantitative of 23 Programs with lines and areas in Work. The research has the time frame delimited between the years 2010 to 2015. The study of the themes related to the Labor Category, in which a total of one hundred and forty-two (142) dissertations were completed. The second moment of the research was on the investigation of the Dissertations defended in the year 2015, which totaled 22 Dissertations, being analyzed: type of research, method, categories of analysis, references used and theoretical current of the authors most used in dissertations. The collection of data was done by means of catalogs of own elaboration. Data analysis took place through the "state of the art" and content analysis. This research has as methodological direction the dialectical historical materialism, by the faithful reading to the method in Marx and in the theoretical construct realized by the Marxist tradition.